AB0138 Altered er stress-induced autophagic reactions are associated with increased apoptosis of t lymphocytes in systemic lupus erythematosus. (23rd January 2014) - Yoo, W.-H.; Sung, M.-S.; Lee, E.-G.; Lee, C.-H.; Lee, M. S.; Cheon, Y.-H.; Lee, S.-I.
Abstract : Background: The autophagic responses to ER stress are involved in the regulation of the maintenance of lymphocyte homeostasis and has been implicated in the pathogenesis of autoimmunity. However, there were no studies about the roles of autophagic responses and its relations with apoptosis of T lymphocytes in systemic lupus erythematosus (SLE). Objectives: Thus, we investigated to study about the pathogenetic roles of ER stress-mediated pathways, autophagic and apoptotic reactions in the T lymphocyte survival and death in SLE. Methods: We investigated the spontaneous and induced autophagic and apoptotic behavior of T lymphocytes from patients with SLE compared with that of T lymphocytes from healthy donors by measuring the autophagymarker microtubule-associated protein 1 light chain 3 (LC3) II and autophagosome by scanning electron microscope. The molecular mechanism of the altered autophagic and apoptotic responses and their relations were investigated in T lymphocyte transfected with siRNA for beclin 1, CHOP and T lymphocyte with overexpression of GRP78 by transfection. The apoptosis, autophagy and ER stress signaling molecules were examined by immunoblotting. Results: There were increased apoptosis and decreased autophagic responses to Thapsigargin (TG) in T lymphocytes from patients with SLE compared with these cells from healthy donors. The activation of ER stress signalingmolecules, including PERK, p-eIF2a, IRE1 and ATF6to TG were decreased in lupus T cells. The expression of anti-apoptotic molecules, Bcl-2, Bcl-XL were decrease and proapoptotic molecules, Bax, caspase-6 were increased in lupus T cells. Our results also revealed that CHOP expression was increased and GRP78 was decreased in lupus T cells. GRP78 overexpression and CHOP siRNA knockdown in T cells from healthy donors were associated with altered apoptotic cell death. Conclusions: Theautophagic and apoptotic responses to TG-induced ER stress are altered and contribute to the abnormal T cell homeostasis with increased apoptotic T cell death. We hypothesize that aberrant autophagic and apoptotic reactions of T lymphocytes to ER stress are involved in the pathogenesis of SLE and might be an important target of treatment. References: Cohen PL. T- and B-cell abnormalities in systemic lupus. J Invest Dermatol. 1993;100(1):69S-72S. Mills JA. Systemic lupus erythematosus. N Engl J Med. 1994;330(26):1871-9. Crispín JC, Liossis SN, Kis-Toth K, Lieberman LA, Kyttaris VC, Juang YT, Tsokos GC. Pathogenesis of human systemic lupus erythematosus: recent advances. Trends Mol Med. 2010;16(2):47-57. Moulton VR, Tsokos GC. Abnormalities of T cell signaling in systemic lupus erythematosus. Arthritis Res Ther. 2011;13(2):207. Krammer PH, Arnold R, Lavrik IN. Life and death in peripheral T cells. Nat Rev Immunol. 2007;7(7):532-42. Pua HH, He YW. Maintaining T lymphocyte homeostasis: another duty of autophagy. Autophagy. 2007;3(3):266-7. Li C, Capan E, Zhao Y, Zhao J, Stolz D, Watkins SC, Jin S, Lu B. Autophagy is induced in CD4+ T cells and important for the growth factor-withdrawal cell death. J Immunol. 2006;177(8):5163-8. Walsh CM, Edinger AL. The complex interplay between autophagy, apoptosis, and necrotic signals promotes T-cell homeostasis. Immunol Rev. 2010;236:95-109. Acknowledgements: Disclosure of Interest: None Declared